INSURANCE OF ATHLETES IN SERBIA - Siniša Ostojić; Natalija Ostojić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The primary purpose of ensuring in sport is to provide financial protection to policyholder individuals (athletes, coaches, referees) and legal entities (sports organizations, federations, clubs) of the negative result of sports injuries and loss of income that athletes or their clubs realize when it comes to clubs' competition, which occur when the risk is realized or the insured event occurs. Injuries are common in sports, we could feel free to call it an integral part of doing a sports activity. Loss of earnings due to sports injuries is extremely high for any professional athlete. In order to be able to return to sports as soon as possible, athletes are forced to set aside large sums of money for rehabilitation, orthopedic supplies and equipment.